2008
DOI: 10.1111/j.1442-9993.2008.01843.x
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance history and stand dynamics in tall open forest and riparian rainforest in the Central Highlands of Victoria

Abstract: Spatial heterogeneity in the intensity of past disturbances has directly influenced the structure and composition of present-day forests around the world. In south-eastern Australia infrequent, high-intensity wildfires are a major part of the historical disturbance regime. While these fires are often assumed to produce even-aged stands, spatial heterogeneity in fire intensity due to highly variable topography may lead to more complex forest age structures. Our study describes the influence of disturbance on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…However, wildfires are highly variable in extent and severity, which is reflected in current stand age structures of a mosaic of even-aged and multi-aged forests [26], [35], [36]. Even-aged stands result from widespread mortality and regeneration following high-severity wildfire.…”
Section: Methodsmentioning
confidence: 99%
“…However, wildfires are highly variable in extent and severity, which is reflected in current stand age structures of a mosaic of even-aged and multi-aged forests [26], [35], [36]. Even-aged stands result from widespread mortality and regeneration following high-severity wildfire.…”
Section: Methodsmentioning
confidence: 99%
“…Eucalypt forests also exhibit multiple age cohorts of trees and distinct structural changes due to heterogeneity in fire history (Simkin and Baker, 2008). In climates where high winter rainfall is followed by a dry summer season, the distribution and abundance of tree species is primarily determined by their ability to tolerate water stress and to re-establish after disturbance (Pigott and Pigott, 1993;Zavala, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In Tasmania, analyses of short term relationships between fire and climate revealed that summer rainfall and indices of the El Nino-Southern Oscillation are important climatic factors influencing the area burnt each summer (Nicholls and Lucas, 2007). Simkin and Baker (2008) demonstrated the use of dendrochronology for precisely deter- Fig. 9.…”
Section: Discussionmentioning
confidence: 99%
“…Hemstrom and Franklin, 1982;Silla et al, 2002;Winter et al, 2002). Old-growth Eucalyptus regnans forests appear to conform to the pattern of infrequent and intense stand replacing fires, yet the precise dates of pre-European fire events which are crucial for characterising the fire regimes of these forests remain largely unknown Simkin and Baker, 2008), reflecting an Australiawide paucity of dendrochronological studies (Pearson and Searson, 2002) and difficulties in applying classical dendrochronological techniques to eucalypts (Brookhouse, 2006). Understanding the return times of stand-replacing fires in E. regnans forests and their relationship with prevailing climatic conditions is critical for contextualising catastrophic fire events in south eastern Australia, such as the recent February 2009 'Black Saturday' fires that burnt vast areas of forest in Victoria, south eastern Australia, with the loss of 173 lives and more than 3000 homes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation